Dramatic recovery after severe descending transtentorial herniation-induced Duret haemorrhage: A case report and review of literature. (March 2014) - Ishizaka, Shunsuke; Shimizu, Tadashi; Ryu, Nobutoshi
Abstract Background: Although Duret haemorrhage of the brainstem caused by descending transtentorial herniation is considered fatal, a few cases have been reported to have good outcome. Moreover, most patients with Duret haemorrhage have severe primary brain injury and the potential outcome of those with mild primary brain injury remains unknown. Case report: This study reports the case of a patient presenting with Duret haemorrhage caused by an idiopathic subdural haematoma who demonstrated dramatic recovery. The patient presented with a low Glasgow Coma Scale score and bilateral oculomotor palsy on admission. Pre-operative CT revealed a large subdural haematoma and Duret haemorrhage of the mid-brain. The subdural haematoma was immediately evacuated under local anaesthesia and the patient demonstrated dramatic post-operative recovery, with no residual quadriparesis and minimal cognitive dysfunction. Interestingly, only bilateral oculomotor palsy persisted. This indicates that Duret haemorrhage restricted to the central portion of the mid-brain without severe primary brain injury has good prognosis. Conclusion: Therefore, patients with Duret haemorrhage of the mid-brain caused by simple subdural haematoma presenting with bilateral oculomotor palsy, including bilateral pupillary dilation, may not always have a poor prognosis.